THE USE OF SONG IN TEACHING SPEAKING FOR PRIMARY SCHOOL STUDENTS - Tuti Aminah Sasmita; Ratih Inayah (IKIP Siliwangi, 2024)
The purpose of this research is to look into the use of song in teaching English to primary school students in greater depth. This study is an action research project done at one of Cimahi's primary schools, class V, with 15 students as participants. Data is collected from each cycle's test results. The findings revealed that incorporating song in the teaching learning process causes students to become more relaxed and active in their interactions, as seen by their greater involvement in class. Another conclusion demonstrated that integrating song, students' English language skills improved from the preliminary to the cycle II stage of the research procedure. The average preliminary score of students is 80.53, and it improved to 86.60 in the second cycle, indicating that all students can accomplish more than the minimal criterion score. It may be stated that integrating songs into the classroom to teach English to primary school students can assist students in improving their English language skills. This study indicates that songs could have been used to teach speaking skills to primary school students in order to improve their English language skills, especially speaking skills.